The Influence of the INFOIMS Web-Based Application on Adolescents' Knowledge About Sexually Transmitted Infections (STIs) (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
This study investigates the effectiveness of the web-based educational application INFOIMS in improving adolescents' knowledge of Sexually Transmitted Infections (STIs) at SMK Kartini in Batam City. The research was driven by the growing concern of high STI prevalence among teenagers and the lack of targeted educational media that suits the digital-native generation. Adolescents often face challenges in accessing comprehensive STI information, leading to gaps in their awareness and understanding of these health risks. This study addresses the issue of inadequate educational resources that effectively engage students in learning about STIs in a manner appropriate for their digital experiences. The primary objective was to assess the INFOIMS application as a tool for improving STI-related knowledge among adolescents. A quasi-experimental research design was employed, using a one-group pre-test and post-test approach. The study involved 36 student participants, who were selected from SMK Kartini in Batam City. Data was collected using pre- and post-intervention questionnaires, and the results were analyzed with the Wilcoxon signed-rank test. The findings revealed a significant improvement in the participants’ knowledge about STIs after using INFOIMS (p-value < 0.05). Initially, many participants exhibited low to moderate levels of knowledge, but after the intervention, all showed a considerable increase in their knowledge, reaching a good level of understanding. These results suggest that the INFOIMS web-based application is an effective tool for improving adolescents' STI health literacy. This study highlights the potential of digital learning tools in school settings to address critical health issues, such as STIs, and shows that web-based applications can offer an innovative solution to enhance adolescent health education. By improving knowledge and awareness, such digital platforms may play a significant role in reducing STI cases among teenagers